Implementasi Model Pembelajaran IPS Berbasis Project-Based Learning dengan Kearifan Lokal di SMPIT BBS Bogor - A'rop, Yusril; Hadi, Syamsul (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This study aims to explore how a local wisdom-based PjBL learning model can improve the effectiveness of social studies learning in a junior high school in Bogor, as well as identify its impact on students' interest, motivation and conceptual understanding. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed using thematic analysis techniques. The results showed that the integration of PjBL with local wisdom successfully increased students' interest and learning motivation, where students showed higher engagement in the learning process and were more active in working on projects relevant to their daily lives. In addition, there is an increase in students' conceptual understanding of social studies materials, which is reflected in the higher average scores of end-of-semester exams and assignments. The projects undertaken by the students, such as the exploration of local history and traditional irrigation systems, successfully connected social studies concepts with real contexts. The conclusion of this study is that the implementation of local wisdom-based PjBL can improve the quality of social studies learning. This learning model not only makes learning more relevant and meaningful, but also helps students develop critical thinking skills and the ability to work together, supporting the application of local wisdom-based PjBL as an effective alternative in social studies learning in Indonesian schools.